Commoncoin: A Semiotic Perspective on its Role in Cooperative Production Relations - Dongo, Eduardo Yalán; Verástegui, Enrique León; De Fazio, Gianluca (Rivista Italiana di Filosofia del Linguaggio, 2023)
The theme of the commons has contemporaneously become a significant area of discussion and interest, particularly in the critique and exploration of alternatives to the logic of capitalist accumulation. A predominant part of the discourse has revolved around the commons, understood in terms of goods (ecological, social, cultural, knowledge). However, it is crucial to emphasize that the commons are not things but social relations. Within the broad topic of the commons, there are initiatives related to common currencies (commoncoin), presented as experiments in appropriating productive forces aimed at the development of alternative technology. Considering that money is a coordinate of unquestionable privilege from the semiotic perspective, semiotic literature has not delved deeply into the semiotic role of money, nor into the meaning management of a complementary currency. This article aims to propose a semiotic theory of commons money from the Marxist and vitalist perspective of Gilles Deleuze and Félix Guattari. To achieve this, a critique is developed against the representative model commonly used to address the semiotic nature of currency, in favor of embracing the notions of extraction and summation suggested by Deleuze and Guattari. The article argues that the concepts of the abstract and the concrete play a significant role in the materialist dialectical method, serving to reflect on community relations related to currency.